Cat-Scratch Disease With Bone Involvemnet - Maia, R (2013)
Background: Bartonella henselae infection typically presents as a self-limiting regional lymphadenopathy. Bone involvement is a very rare form of the disease. Aims: To describe bone infection associated to cat-scratch disease (CSD) in a portuguese pediatric hospital. Methods: Clinical records of children admitted at the hospital with the diagnosis of CSD associated bone infection, during 2010, were reviewed. Diagnosis was confirmed by serology using indirect fluorescence assay and nucleic acid amplification from lymph node biopsy. Results: Two boys, 2 and 7 years old, were identified. One had prolonged fever and neck pain. MRI suggested D6-D9 osteomyelitis. Cultures were negative and Mycobacterium tuberculosis and Brucella infection were excluded. He was treated with gentamicin and cotrimoxazol, with clinical, but no significant image, improvement. The second child presented subacute sternoclavicular swelling and mildly enlarged axillary lymph nodes. Image studies revealed an osteolytic lesion of the clavicle and hypoechogenic splenic lesions. Histopathology of lymph node showed granulomatous adenitis and excluded malignancy. Therapy with azythromicin and rifampicin was successful. Both had contact with cats. Primary and secondary immunodeficiency was excluded. Conclusion: The optimal therapy for atypical Bartonella henselae infection is unknown and the role of antibiotics uncertain. Several combinations of antibiotics have been proposed for bone disease treatment, but recommendations are lacking. The different outcome in the presented cases could be related with the distinct therapeutic regimens used. Although atypical infection has classically been associated with immunodeficiency, this has not been the rule in bone disease and the need for extensive evaluation must be reviewed.